Beneficial effects of ginsenosides on diabetic nephropathy: A systematical review and meta-analysis of preclinical evidence. (10th February 2023) - Chen, Xiao-Mei; Lin, Gui-Xuan; Wang, Xue; Ma, Hong-Yan; Wang, Ru-Shang; Wang, Shu-Mei; Tang, Dan
Abstract: Ethnopharmacological relevance: Ginseng is one of the most widely used herbs in the world for the treatment of various diseases, and ginsenoside is the representative bioactive component in ginseng. There have been many in vivo studies on ginsenoside for the treatment of diabetic nephropathy (DN), the most common diabetic microvascular complication and the main cause of diabetic morbidity and mortality. Aim of the study: The purpose of this study is to evaluate the efficacy of ginsenosides on DN by preclinical evidence and meta-analysis. Meanwhile, the main possible action mechanisms of ginsenosides against DN were also summarized. Materials and methods: We systematically searched PubMed, WOS, Embase, Cochrane, WanFang, Cqvip, CNKI and CBM databases from January 1, 2000, to November 15, 2021, to evaluate the animal experiments of ginsenosides for the treatment of DN. Finally, 30 animal experiments were included. Twelve outcome measures, including renal function indicators (24-h urine protein, serum creatinine, urea nitrogen, creatinine clearance, uric acid, urinary albumin to creatinine ratio), oxidative stress biomarkers (GPX, MDA, SOD), inflammatory factors (IL-1, IL-6, TNF-α) were obtained by using RevMan 5.4 software for meta-analysis. Results: The results showed that except for no significant difference in CCr, other indicators such as 24h UP, SCr, blood urea nitrogen, uric acid and UACR were significantly decreased. It showed that ginsenoside could improve renal function in diabetes. Meanwhile ginsenoside significantly up-regulated antioxidant enzymes SOD and GPX, down-regulated MDA and inflammatory factors IL-1, IL-6 and TNF-α, indicating that ginsenoside may have antioxidant and anti-inflammatory effects. Conclusion: Ginsenoside can protect against the renal failure in diabetes through anti-inflammation, anti-oxidation, anti-renal fibrosis, anti-apoptosis/pyroptosis, regulation of blood glucose/lipid metabolism, etc. Which provides preclinical evidence for the application of ginsenoside in the treatment of DN. Graphical abstract: Image 1 Highlights: Efficacy and mechanisms of ginsenosides on DN was evaluated by systematical review and meta-analysis. Preclinical evidence suggests ginsenosides can be used for treating DN. Ginsenoside can treat DN through anti-inflammation, anti-oxidation, anti-renal fibrosis, etc.